3D effects of edge magnetic field configuration on divertor/scrape-off layer transport and optimization possibilities for a future reactor. (29th September 2015) - Kobayashi, M.; Xu, Y.; Ida, K.; Corre, Y.; Feng, Y.; Schmitz, O.; Frerichs, H.; Tabares, F.L.; Evans, T.E.; Coenen, J.W.; Liang, Y.; Bader, A.; et al.
Abstract: This paper assesses the three-dimensional (3D) effects of the edge magnetic field structure on divertor/scrape-off layer transport, based on an inter-machine comparison of experimental data and on the recent progress of 3D edge transport simulation. The 3D effects are elucidated as a consequence of competition between transports parallel ( ) and perpendicular ( ) to the magnetic field, in open field lines cut by divertor plates, or in magnetic islands. The competition has strong impacts on divertor functions, such as determination of the divertor density regime, impurity screening and detachment control. The effects of magnetic perturbation on the edge electric field and turbulent transport are also discussed. Parameterization to measure the 3D effects on the edge transport is attempted for the individual divertor functions. Based on the suggested key parameters, an operation domain of the 3D divertor configuration is discussed for future devices.